1983
DOI: 10.1083/jcb.97.3.627
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial transport of a viral membrane glycoprotein implanted into the apical plasma membrane of Madin-Darby canine kidney cells. I. Morphological evidence.

Abstract: The G protein of vesicular stomatitis virus was implanted in the apical plasma membrane of Madin-Darby canine kidney cells by low pH-dependent fusion of the viral envelope with the cellular membrane. The amount of fusion as determined by removal of unfused virions, either by tryptic digestion or by EDTA treatment at 0°C, was 22-24% of the cell-bound virus radioactivity. Upon incubation of cells after implantation, the amount of G protein as detected by immunofluorescence diminished on the apical membrane and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 38 publications
(38 reference statements)
1
57
0
Order By: Relevance
“…BFA did stimulate to some extent cellular accumulation of HRP in highly confluent MDCK cells grown on plastic (not shown). Under these conditions the plasma membrane facing the medium bears resemblance to the apical membrane of truly polarized MDCK cells (22).…”
Section: Ultrastructural Analysis Of Endosomes and Lysosomes In Bfa-tmentioning
confidence: 99%
“…BFA did stimulate to some extent cellular accumulation of HRP in highly confluent MDCK cells grown on plastic (not shown). Under these conditions the plasma membrane facing the medium bears resemblance to the apical membrane of truly polarized MDCK cells (22).…”
Section: Ultrastructural Analysis Of Endosomes and Lysosomes In Bfa-tmentioning
confidence: 99%
“…Further, studies on epithelial cells showed that GSL [12][13][14] and glycosylphosphatidylinositol (GPI)-anchored proteins [15,16] were preferentially target to the apical membrane. Moreover, biologically active membrane proteins were found to be associated with surrounding GSLs [17].…”
Section: Gsl-enriched Microdomains: From Caveolae To Raft To Glycosmentioning
confidence: 99%
“…1. First observations of polarized sorting of GSL [12][13][14] and glycoproteins [15,16] in epithelial cells. 2.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…To generate radioactively labeled retrovirus for binding studies, purification of retrovirus is required. We addressed this requirement by applying a method previously described for the purification of vesicular stomatitis virus (17) that uses ultracentrifugation and a sucrose-step gradient to purify viral particles within the interphase of the gradient. First, localization of infectious retrovirus in the different fractions of the gradient after centrifugation was analyzed.…”
Section: Fibronectin Fragments Have Been Shown To Improve Retrovirus mentioning
confidence: 99%